(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The Author analyzes what can be pieced out from the rich thought of the great jurist Stefano Rodotà, that may help to reflect critically about fundamentals and limits of Bio-Criminal Law. This approach eventually reveals how unsuitable is Criminal Law to discipline the problematic area of bioethical issues.